A 16S rRNA gene sequencing based study of oral microbiota in migraine patients in China. Issue 1 (1st January 2021) - Jiang, Weiqing; Wang, Tingting; Liu, Chen; Deng, Mingzhu; Ren, Xiao; Wang, Fei; Zhang, Yaqing; Yu, Xueying; Yao, Lingling; Wang, Yonggang
ABSTRACT: Migraine is a primary headache characterized by moderate or severe headache attacks, accompanied with reversible neurological and systemic symptoms. There are rare biomarkers for the disease. While emerging evidence has indicated the connection between gut microbiota and migraine, the relation between oral microbiota and migraine is barely known. Thus, the objective of the current study was to explore a possible correlation between oral microbiota and migraine. We compared the oral microbiota communities of migraine patients (26) with healthy subjects (29) via 16S rRNA gene sequencing. Alpha diversity indices were higher in migraine group compared with control group, whereas beta diversity indices also showed significant difference. A total of 23 genera were found differentially abundant between migraine and control groups. To conclude, there was a significant compositional difference in oral microbiota in migraine patients compared with healthy subjects. GRAPHICAL ABSTRACT: uf0001